Rules and regulations subject to the provisions of the deed poll [electronic resource] - Hudson's Bay Company.; Wrigley, J. ([Winnipeg? : s.n.], 1887)
Signed: J. Wrigley, Commissioner. Cover title. Electronic reproduction. Mode of access: Internet. 44